(untitled) (Analysis of International Sciences, 2025)
This article explores the pedagogical foundations of sports activities conducted with students. It analyzes the impact of sports training on students’ physical, mental, and social development, the pedagogical principles of organizing sports events, and the role of sports in the educational process. The article also examines the role of the teacher-coach in sports training and the issues of an individual approach to students.